2015
DOI: 10.1007/s00520-015-3044-7
|View full text |Cite
|
Sign up to set email alerts
|

A web-based intervention (RESTORE) to support self-management of cancer-related fatigue following primary cancer treatment: a multi-centre proof of concept randomised controlled trial

Abstract: PurposeCancer-related fatigue (CRF) is a frequent and distressing symptom experienced after cancer treatment. RESTORE is the first web-based resource designed to enhance self-efficacy to manage CRF following curative-intent treatment. The aim of this study is to test the proof of concept and inform the design of an effectiveness trial.MethodsA multi-centre parallel-group two-armed (1:1) exploratory randomised controlled trial (RCT) with qualitative process evaluation was employed in the study. Participants (≥1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
217
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(222 citation statements)
references
References 32 publications
3
217
2
Order By: Relevance
“…The trials were published between 2005–2018. Trials were undertaken in the USA (Bantum et al, ; Owen et al, ; Smith et al, ; Somers et al, ; Syrjala et al, ), Netherlands (Admiraal et al, ; van der Berg et al, ; Boele et al, ; Golsteijn et al, ; Willems et al, ), UK (Foster et al, ), Canada (Vallerand et al, ), China (Zhang et al, ; Zhu et al, ), and South Korea (Lee et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trials were published between 2005–2018. Trials were undertaken in the USA (Bantum et al, ; Owen et al, ; Smith et al, ; Somers et al, ; Syrjala et al, ), Netherlands (Admiraal et al, ; van der Berg et al, ; Boele et al, ; Golsteijn et al, ; Willems et al, ), UK (Foster et al, ), Canada (Vallerand et al, ), China (Zhang et al, ; Zhu et al, ), and South Korea (Lee et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Participants in four trials were patients with any cancer (Foster et al, ; Bantum et al, ; Somers et al, ; Willems et al, ). The other eleven trials focused on specific cancers: breast cancer (Admiraal et al, ; van den Berg et al, ; Lee et al, ; Owen et al, ; Smith et al, ; Zhu et al, ), glioma (Boele et al, ), haematological cancer (Syrjala et al, ; Vallerand et al, ), rectal cancer (Zhang et al, ), and both colorectal cancer and prostate cancer (Golsteijn et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In addition, explorative analyses of a feasibility RCT by Foster et al 6 demonstrated that a Web-based self-management intervention enhanced the self-efficacy of cancer survivors in managing fatigue compared with a patients with a control condition who only received an information leaflet. However, the effects of other types of Web-based interventions aimed at fatigue in cancer survivors are promising.…”
Section: Introductionmentioning
confidence: 99%
“…David, Schlenker, Prudlo, & Larbig, 2013;Wootten et al, 2015), indicating a need for further development and evaluation. Online interventions for people affected by cancer vary widely, with some focused on cancer survivors generally (Beatty, Kemp, Wade, & Koczwara, 2015;Willems et al, 2015), some focused on a specific issue such as fatigue (Foster et al, 2016) and others focused on people affected by a particular type of cancer, such as breast (Fergus et al, 2014) or prostate cancer (Wootten et al, 2015). Online interventions for people affected by cancer vary widely, with some focused on cancer survivors generally (Beatty, Kemp, Wade, & Koczwara, 2015;Willems et al, 2015), some focused on a specific issue such as fatigue (Foster et al, 2016) and others focused on people affected by a particular type of cancer, such as breast (Fergus et al, 2014) or prostate cancer (Wootten et al, 2015).…”
Section: Introductionmentioning
confidence: 99%